Mulinane- and Azorellane-Type Diterpenoids: A Systematic Review of Their Biosynthesis, Chemistry, and Pharmacology - Dzul-Beh, Angel de Jesús (Biomolecules, 2020)
Mulinane- and azorellane-type diterpenoids have unique tricyclic fused five-, six-, and seven-membered systems and a wide range of biological properties, including antimicrobial, antiprotozoal, spermicidal, gastroprotective, and anti-inflammatory, among others. These secondary metabolites are exclusive constituents of medicinal plants belonging to the Azorella, Laretia, and Mulinum genera. In the last 30 years, more than 95 mulinanes and azorellanes have been reported, 49 of them being natural products, 4 synthetics, and the rest semisynthetic and biotransformed derivatives. This systematic review highlights the biosynthetic origin, the chemistry, and the pharmacological activities of this remarkably interesting group of diterpenoids.